Influence of carbon addition on mechanical properties in ultra-fine WC-Co cutting insert / Nur Atikah Muin - Muin, Nur Atikah (2017)
Tungsten carbide-cobalt (WC-Co) are used as cutting tools because of a combination of desirable high hardness and high fracture toughness due to the respective contributions of the carbide and metallic phases. The mechanical properties of these materials depend on their composition and microstructure especially on the grain size of the carbide phase. The addition of specific metallic would lead to further improvement of its mechanical properties. In this work, the influence of Carbon (C) addition in WC-Co composite on mechanical properties in ultrafine WC-Co composite was studied. The percentages of carbon are varied at 0%, 0.1%, 0.2%, 0.3%, and 0.4% The samples were prepared using powder metallurgy routes with involving mixing, drying and sieving, compaction, cold isostatic pressing (CIP) and sintering. Mechanical properties such as hardness, transverse rupture strength (TRS), density and microstructure were measured. The hardness is measured using Vickers Hardness tester while the TRS is determined using Universal Testing Machine. In addition, the density is measured using Electronic Densimeter and the microstructure is observed using Scanning Electron Microscope. It exhibits that the hardness of WC-Co composite is decreased with the increasing of carbon percentages. The maximum hardness is gain at the composition of 0.1%C. A similar trend was observed for TRS and density.